LAPORAN EVALUATIF JAMINAN KESEHATAN NASIONAL DI KALIMANTAN SELATAN: ANTARA KEPESERTAAN TINGGI DAN RISIKO KEBERLANJUTAN TAHUN 2025 - Ahyar Wahyudi; Rasyid Ridha; Ristanti Sulistyo Rini; Arlan Prabowo (Kirana Publisher, 2026)
Universal Health Coverage (UHC) is a cornerstone of health development, ensuring that all citizens can access needed health services without financial hardship. Administratively, South Kalimantan Province achieved a UHC coverage rate of 99.59 percent in 2025, with several districts exceeding 100 percent. This report aims to critically examine this achievement by situating it within the sustainability framework of Indonesia’s National Health Insurance (JKN). The study employs a descriptive–analytical policy evaluation approach, drawing on secondary data from provincial JKN implementation reports, policy documents, and national and international literature. The findings indicate that high administrative coverage does not necessarily translate into substantive health protection. Structural challenges were identified, including data validity anomalies, a substantial proportion of inactive participants, and financial vulnerability among informal sector workers. Participant inactivity emerges as a key weakness undermining effective UHC, while fragmented data systems and rigid subsidy designs exacerbate the risk of hidden exclusion. The report concludes that post-achievement UHC success requires a paradigm shift from enrollment expansion toward strengthened governance, sustainable financing, and effective, equitable health protection. Without such adjustments, high coverage figures risk becoming an administrative illusion rather than a guarantee of long-term health security.